2017
DOI: 10.1177/1367493517717078
|View full text |Cite
|
Sign up to set email alerts
|

Stories of survival: Children’s narratives of psychosocial well-being following paediatric critical illness or injury

Abstract: Survival from critical illness can expose children to an array of negative physical and psychological problems. While the perspective of parents and professionals have been well documented, there is limited understanding of how childhood critical care survivors make sense of their experiences in relation to psychosocial well-being. We aimed to explore long-term psychosocial well-being of childhood survivors of critical illness through their stories. A qualitative, exploratory study using serial in-depth interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…This is an intentionally Of note, studies typically assess emotional health indirectly using measures of health related quality of life (HRQoL) which incorporate elements of physical health, functional status, behavior, and psychosocial health rather than using mental health specific measures. [9] We add 'social health' as a fourth domain in PICS-p to acknowledge the burgeoning evidence that critical illness impacts the child's and family's social functioning [10][11][12] in relation to re-integration with peers; child and families' social capital; and the economic impact of unemployment on families when a caregiver has to give up work to care for a child. Undoubtedly, family stress, resilience, and outcomes are intricately intertwined.…”
Section: Childhood -A Dynamic Statementioning
confidence: 99%
“…This is an intentionally Of note, studies typically assess emotional health indirectly using measures of health related quality of life (HRQoL) which incorporate elements of physical health, functional status, behavior, and psychosocial health rather than using mental health specific measures. [9] We add 'social health' as a fourth domain in PICS-p to acknowledge the burgeoning evidence that critical illness impacts the child's and family's social functioning [10][11][12] in relation to re-integration with peers; child and families' social capital; and the economic impact of unemployment on families when a caregiver has to give up work to care for a child. Undoubtedly, family stress, resilience, and outcomes are intricately intertwined.…”
Section: Childhood -A Dynamic Statementioning
confidence: 99%
“…It is noted in the literature that children's needs are synergistically interconnected to their parents' needs which was evident in this study when children reported on their parents' needs as being important in the factor “resources”; however, it is important to state that the newly developed NCQ (16‐item) is a tool to measure CCC and not an adaptation of the NPQ for children (Foster & Whitehead, ; Nilsson et al, ; Soderback et al, ). When using the NCQ, the authors recommend to explore for any relationship between the NCQ importance and fulfilment scores, as a need scored as important and not met may predict a child's hospital experience and health outcome more than demography or illness severity (Manning, Hemingway, & Redsell, , ).…”
Section: Discussionmentioning
confidence: 99%
“…As advocated in the literature, art-based approaches (draw and tell, graphic elicitation) will be used to facilitate the involvement and verbal responses from child participants 38 39. The focus of the semi-structured interviews will be on exploring the following areas: (1) experience of injury; (2) frustrations of recovering and (3) features of recovery and positive and negative outcomes.…”
Section: Methods and Designmentioning
confidence: 99%